Literature Review: Faktor Sanitasi Kapal dengan Keberadaan Vektor di Kapal - Rofiatul Asrifah; Novera Herdiani (KESMAS UWIGAMA: Jurnal Kesehatan Masyarakat, 2021)
Background: Ship are related to public health because they allow the spread of disease due to public health risk factors, one of which is the presence of vectors that can trigger disease exchange in human. The existence of vectors on board is caused by poor sanitation such as bad hygiene, inadequate lighting and ventilation, bad food storage, and scattered garbage that is not properly disposed of. Objectives: This literature review aims to determine the relationship between ship sanitation factors and the presence of vectors on ship Research Metodes: This study use the literature review method by searching for journals on the google scholar database and one search (2010-2020). The keyword used are "ship sanitation with vector presence", "ship sanitation and presence of vectors" and "ship and vector sanitation". Results: The result obtained on google scholar 150 articles and one search 16 articles where only 11 articles match this study. The result of this study, unqualified ship compartments namely kitchen and warehouse, due to ineligible hygiene, do not have adequate trash cans, and are free of insects and rat. The presence of cockroach vectors tends to be found on passenger ships and the presence of mosquito and mouse vectors tends to be found on cargo ship. Conclusion: The conclusion in this study is that ship sanitation factors are related to the existence of vectors. The advice given is to increase routine ship sanitation checks by the Port Health Office officers.